The mitral inflow E/A ratio before the procedure may predict late recurrence after pulmonary vein isolation using second-generation cryoballoon. (19th May 2022) - Ulus, T; Yilmaz, AS; Sener, E; Yalvac, HE; Camli, E; Durmaz, FE; Cavusoglu, Y
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The left ventricular (LV) diastolic dysfunction (DD) increases the risk of atrial fibrillation (AF) development. Some studies investigated whether a relationship between DD and late recurrence after catheter ablation for AF, but they found conflictory results. Such studies had relatively short follow-up duration and they did not have a standard ablation protocol. Some patients were taken to PVI only, while additional linear lesions in localizations such as the left atrial (LA) roof, LA isthmus, and cavotricuspid isthmus were added in others. Purpose: The mitral inflow E/A ratio is a simple and practical method commonly used to evaluate LV DD. We aimed to investigate whether the E/A ratio before the procedure was predictive for late recurrence in patients with AF undergoing pulmonary vein isolation (PVI) with cryoballoon (CB). Methods: A total of 100 patients undergoing AF ablation for the first time using second-generation CB were included. Only patients with paroxysmal AF and sinus rhythm the day before the procedure, and with pre-procedural pro-B natriuretic peptide levels within normal limits were included. The patients with and without late recurrence were compared in terms of basal characteristics and procedural features. Any atrial tachyarrhythmia episode longer than 30 s after the blanking period was defined as late recurrence. Results: The patients [age: 58.0 (50.2-62.0) years, 53 female] were followed up for a median of 44.5 (14.2-62.7) months and late recurrence developed in 25 patients. Female gender (72.0% vs 46.7%), hypertension (72.0% vs 48.0%), and the frequency of early recurrence (20.0% vs 4.0%) were found to be higher in patients with late recurrence than in those without it (p =0.028, 0.037 and 0.022, respectively). The CHA2DS2-Vasc score was higher [2.0 (1.0-3.0) vs 1.0 (0-2.0)], AF duration was longer (27.8 ± 9.4 vs 22.0 ± 8.4 months) and the E/A ratio was lower [0.5 (0.4-1.2) vs 1.4 (0.6-1.7)] in patients with late recurrence than in those without it (p=0.014, 0.006 and 0.001, respectively) (Figure 1). The groups were similar in terms of precedural features. A multivariate analysis showed that female gender (HR: 4.46, 95%CI: 1.24-15.97, p=0.021), early recurrence (HR: 10.22, 95% CI: 2.49-41.99, p=0.001), and E/A ratio (HR: 0.25, 95%CI: 0.11-0.57, p=0.001) were independent predictors for late recurrence (Figure 2). Receiver operating characteristic analysis showed that the optimal cut-off level of the E/A ratio was 0.84. Any ATa free survival rate was significantly lower in patients with E/A ratio <0.84 than in those with ≥0.84 (56.1% vs 88.1%, log-rank p<0.001). Conclusions: Female gender, early recurrence, and E/A ratio are independent predictors of late recurrence in patients with AF undergoing PVI using second-generation CB. Measuring the E/A ratio in patients with sinus rhythm before AF ablation may help to predict future recurrences.